Consequences of Public Sector Employees' CSR Perceptions in a Developing Country: Organizational Benefits and Beyond. Issue 2 (4th March 2023) - Grabner-Kräuter, Sonja; Tafolli, Festim; Breitenecker, Robert J.
Abstract: This study contributes to the growing literature related to demands for social responsibility in the public sector in a developing country context. We report on a qualitative and a quantitative study conducted in the public sector in Kosovo to investigate, first, whether public sector organizations strive for CSR engagement, and second, whether and how employees' perceptions of their employers' CSR engagement affect various employee outcomes. The results of the qualitative content analysis of the mission statements of 20 public sector organizations in terms of CSR-related information they contain show that the public sector organizations have included both internal and external CSR elements in their mission statements. The quantitative study uses survey data collected from 126 employees in public sector organizations in Kosovo. The findings support the serial mediation of organizational trust and job satisfaction on the negative relationship between employees' perceptions of internal and external CSR and intention to emigrate. From a practical perspective, the findings encourage public sector organizations to increase their CSR engagement to achieve positive employee outcomes, both in relation to their own organization and beyond.